PENGGUNAAN METODE PEMBELAJARAN MUSYAWARAH PADA KITAB SAFINATUN NAJA UNTUK MENINGKATKAN PEMAHAMAN SANTRI MDTA HIDAYATUSSHIBYAAN DESA MANUNGGA - Ahmad Assyatibi, Mesran, Susanti Nirmalasari (FKIP UMN ALWASHLIYAH, 2026)
This study aims to determine the effectiveness of the musyawarah (deliberation) learning method in improving students‟ understanding of the Safinatun Naja book at MDTA Hidayatusshibyaan, Desa Manunggal. Safinatun Naja is a Shafi'i school of thought fiqh book that is widely used in madrasahs as a foundation for worship learning. However, the complexity of its language and structure presents a challenge for students in comprehending the material. To address this, a learning method that encourages active student participation and provides space for critical thinking and collaborative discussion is needed. This research employed a descriptive qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation from the Head of the Madrasah and teachers directly involved in the learning process. The results showed that the application of the musyawarah method improved students‟ understanding of the book‟s content, fostered active learning, and cultivated democratic attitudes and shared responsibility. Students not only learned from the teacher but also from peer interaction through discussions and idea exchanges. Supporting factors for the success of this method include the teacher‟s role as a facilitator, a conducive classroom atmosphere, and the preparation of materials relevant to students‟ lives. Inhibiting factors include limited learning time, differences in students‟ comprehension levels, and a lack of confidence among some students in expressing their opinions. Thus, the musyawarah learning method proves to be an effective strategy for improving understanding of the Safinatun Naja book when applied in a structured manner and adapted to learners‟ needs.